Radiological Evaluation of Bone Mineral Density in Diabetic Patients with Chronic Musculoskeletal Pain: A Cross-Sectional Study - Aisha Asim, Salman Habib Abbasi, Saima Begum, Muhammad Asad Khan, Ratan Kumar Ramani, Kaneez Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus is associated with multiple systemic complications, including significant effects on musculoskeletal health. Chronic musculoskeletal pain is common among diabetic patients and may indicate early skeletal fragility. Radiological evaluation of bone mineral density (BMD) provides valuable insight into the extent of bone involvement in this population. Objective: To evaluate bone mineral density in diabetic patients presenting with chronic musculoskeletal pain and to determine the association of BMD with diabetes duration, glycemic control, and body mass index. Methods: A cross-sectional study was conducted in the Department of Radiology in collaboration with the Department of Medicine at Al-Nafees Medical College and Hospital, Islamabad, from June 2022 to May 2023. A total of 100 patients with type 2 diabetes mellitus and musculoskeletal pain persisting for more than three months were included. Demographic and clinical data were collected, and BMD was measured at the lumbar spine and femoral neck using dual-energy X-ray absorptiometry (DEXA). Patients were categorized as normal, osteopenic, or osteoporotic according to WHO criteria. Data were analyzed using SPSS version 26, with p < 0.05 considered statistically significant. Results: The mean age of participants was 55.8 ± 9.6 years, with a female predominance (56%). Normal BMD was found in 30% of patients, while 44% had osteopenia and 26% had osteoporosis. Reduced BMD was significantly associated with longer diabetes duration (≥10 years; p < 0.05) and poor glycemic control (HbA1c > 7.5%; p < 0.05). Female patients and those with lower BMI were more likely to exhibit osteoporosis, while obese individuals showed preserved hip BMD but reduced lumbar spine density. Conclusion: Osteopenia and osteoporosis are highly prevalent in diabetic patients with chronic musculoskeletal pain. Duration of diabetes, poor glycemic control, and low BMI are key risk factors associated with reduced BMD. Routine radiological evaluation using DEXA is strongly recommended in such patients to enable early diagnosis and preventive management of osteoporosis. Keywords: Diabetes mellitus, Bone mineral density, Osteopenia, Osteoporosis, Musculoskeletal pain, DEXA